Концептуальна модель синтезу системи офісів з управління програмами - Петренко, Юрій Антонович (НТУ "ХПІ", 2015)
В статті, в межах розвитку методології управлення програмами та формалізації процесу синтезу системи офісів з управління програмами (СОУП) проведено теоретико-множинне його описання. Системна концепція синтезу СОУП у вигляді моделей, що наведена у статті є досить загальна, та становить принципи декомпозиції її на часткові задачі, такі як вибір оргструктур і рівня функціональних повноважень офісу, технології реалізації процесів управління проектами, встановлення комунікацій між ними, вибору місця розташування, підбір кваліфікованих виконавців. Для отримання по ним рішень потрібна подальша їх деталізація та конкретизація.

In an article, in the development of methodology for program management and formalization of the process of synthesis of program management offices (SPMO) the set-theoretic description are carried out. These conceptual models provide a single formalized representation of the hierarchical structure of the program, bring a systematization to the complex semi-structured program management process and allow to get an idea of the dimension and complexity of the problem and its alternative solutions. To make these solutions in the synthesis of the single criterion SPMO positions functional and costly performance benchmarks of the SMPO option effectiveness are defined and formalized which, unlike the existing ones, permit to perform multi-factor evaluation of the effectiveness and to choose a compromise with the maximum quality, minimum time and cost.System concept of SMPO synthesis in the form of models that are presented in the article is sufficiently general and defines the principles of its decomposition into specific tasks, such as selection of organizational structures and level of functional office authority, technology of implementation of the project management processes, communication setting between them, selection of the location, selection of qualified performers. To get the solutions further specification is needed.
Conceptual model of synthesis of program management offices
Keywords: система проектних офісів; системна концепція; теоретико-множинний опис; часткові задачі; system concept; set-theoretic description; program management; project office